Tantangan Gugatan Cerai Ghaib: Analisis Putusan dan Implikasi Hukumnya di Indonesia - Mangarengi, Arianty Anggraeny; Hamzah, Yuli Adha; Nursyam, Aldifa Nanda (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aimed to analyze the legal basis and considerations of judges in deciding ghoib divorce cases and their legal consequences for the parties involved. This study combines normative and empirical research methods. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results showed that in deciding ghoib divorce cases, the Panel of Judges considered various aspects balanced, including the reasons for divorce given by the plaintiff and witness testimony. The judge made the appropriate decision by verstek, granting the ghoib divorce lawsuit and imposing talaq one ba’in sughra. The legal consequences of ghoib divorce refer to Article 119 of the Compilation of Islamic Law, which regulates talaq ba’in sughra, while Law Number 1 of 1974 and the Civil Code only regulate the legal consequences of divorce in general. Therefore, it is recommended that judges consistently adhere to the principles of justice and caution when handling ghoib divorce cases. Married couples must realize that disappearing without a trace is not a wise solution and will only complicate problem-solving. Divorce should be pursued as a last resort after all efforts to maintain the household have failed. Furthermore, the government needs to create more transparent and comprehensive rules and guidelines regarding the ghoib divorce trial process in Religious Courts to avoid legal uncertainty and ensure the protection of all parties’ rights.